Amphetamine increases blood pressure and heart rate but has no effect on motor recovery or cerebral haemodynamics in ischaemic stroke: a randomized controlled trial (ISRCTN 36285333) - Sprigg, Nikola; Willmot, Mark; Gray, Laura J.; Sunderland, Alan; Pomeroy, Val; Walker, Marion; Bath, Philip M.W. (Nature Publishing Group, 2007)
Amphetamine enhances recovery after experimental ischaemia and has shown promise in small clinical trials when combined with motor or sensory stimulation. Amphetamine, a sympathomimetic, might have haemodynamic effects in stroke patients, although limited data have been published. Subjects were recruited 3-30 days post ischaemic stroke into a phase II randomised (1:1), double blind, placebo-controlled trial. Subjects received dexamphetamine (5mg initially, then 10mg for 10 subsequent doses with 3 or 4 day separations) or placebo in addition to inpatient physiotherapy. Recovery was assessed by motor scales (Fugl-Meyer, FM), and functional scales (Barthel index, BI and modified Rankin score, mRS). Peripheral blood pressure (BP), central haemodynamics and middle cerebral artery blood flow velocity were assessed before, and 90 minutes after, the first 2 doses. 33 subjects were recruited, age 33-88 (mean 71) years, males 52%, 4-30 (median 15) days post stroke to inclusion. 16 patients were randomised to placebo and 17 amphetamine. Amphetamine did not improve motor function at 90 days; mean (standard deviation) FM 37.6 (27.6) vs. control 35.2 (27.8) (p=0.81). Functional outcome (BI, mRS) did not differ between treatment groups. Peripheral and central systolic BP, and heart rate, were 11.2 mmHg (p=0.03), 9.5 mmHg (p=0.04) and 7 beats/minute (p=0.02) higher respectively with amphetamine, compared with control. A non-significant reduction in myocardial perfusion (Buckberg Index) was seen with amphetamine. Other cardiac and cerebral haemodynamics were unaffected. Amphetamine did not improve motor impairment or function after ischaemic stroke but did significantly increase BP and heart rate without altering cerebral haemodynamics.